Re-engineering systems for the treatment of depression in primary care: cluster randomised controlled trial. Issue 7466 (2nd September 2004) - Dietrich, Allen J; Oxman, Thomas E; Williams, John W; Schulberg, Herbert C; Bruce, Martha L; Lee, Pamela W; Barry, Sheila; Raue, Patrick J; Lefever, Jean J; Heo, Moonseong; Rost, Kathryn; Kroenke, Kurt; et al.
Abstract: Objective To test the effectiveness of an evidence based model for management of depression in primary care with support from quality improvement resources. Design Cluster randomised controlled trial. Setting Five healthcare organisations in the United States and 60 affiliated practices. Patients 405 patients, aged ≥ 18 years, starting or changing treatment for depression. Intervention Care provided by clinicians, with staff providing telephone support under supervision from a psychiatrist. Main outcome measures Severity of depression at three and six months (Hopkins symptom checklist-20): response to treatment (≥ 50% decrease in scores) and remission (score of < 0.5). Results At six months, 60% (106 of 177) of patients in intervention practices had responded to treatment compared with 47% (68 of 146) of patients in usual care practices (P = 0.02). At six months, 37% of intervention patients showed remission compared with 27% for usual care patients (P = 0.014). 90% of intervention patients rated their depression care as good or excellent at six months compared with 75% of usual care patients (P = 0.0003). Conclusion Resources such as quality improvement programmes can be used effectively in primary care to implement evidence based management of depression and improve outcomes for patients with depression.